Preparation method of high-entropy iron-aluminum layered double hydroxide loaded iron-sodium catalyst and application of catalyst in carbon dioxide hydrogenation catalysis
Preparation of high-entropy iron-aluminum layered double hydroxide-supported iron-sodium catalysts through co-precipitation method, solving the problem of insufficient conversion and selectivity of existing iron-based catalysts in carbon dioxide hydrogenation reaction, and achieving high conversion and selectivity The improvement, especially in O/P, demonstrates high thermal stability and high specific surface area.
Patent Information
- Application Number
- CN202411490450.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-03
AI Technical Summary
The existing iron-based catalysts have insufficient conversion and selectivity in the hydrogenation of carbon dioxide to olefins, especially in O/P, and high entropy layered dihydroxides have not been studied in this field.
A high-entropy iron-aluminum layered double hydroxide-supported iron-sodium catalyst was prepared by one-step co-precipitation method. By adjusting the pH value and calcining conditions, a high-entropy iron-aluminum layered double hydroxide-supported iron-sodium catalyst with spinel structure was formed. , improve its activity and selectivity in carbon dioxide hydrogenation reaction.
It significantly improves the conversion rate and selectivity of carbon dioxide hydrogenation reaction, especially in terms of O/P, the catalyst has high thermodynamic stability and high specific surface area, and is suitable for industrial production.
Smart Images

Figure BDA0005099896820000071 
Figure BDA0005099896820000081 
Figure HDA0005099896950000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new material preparation technology and application, and specifically relates to a preparation method and application of a high-entropy iron-aluminum layered double hydroxide-loaded iron-sodium catalyst. Background Art
[0002] The continuous consumption of fossil fuels has led to an increasing concentration of CO2 in the atmosphere, and environmental problems are becoming increasingly serious. Fischer-Tropsch synthesis (FTS) can convert CO2+H2 into valuable chemicals such as olefins, methanol, gasoline, etc., and can reduce CO2 emissions and alleviate the greenhouse effect. Since iron-based catalysts have the active phase of FTS and have a good effect in the hydrogenation of carbon dioxide to olefins, a large number of researchers have studied them. In addition, the addition of some additives has a good promoting effect on the performance of carbon dioxide hydrogenation. For example, Yang et al. reported iron-based catalysts modified with transition metals (zinc, copper, manganese) and sodium for the hydrogenation of carbon dioxide to olefins. The study found that Zn and Cu modifiers can promote the reduction and carburization of iron catalysts, which is conducive to the formation of Fe3O4 and Fe5C2 active phases. Although the introduction of Mn enhances the reducibility of iron oxides, the strong interaction between Mn and iron species is not conducive to the further conversion of CO in the intermediate. The FeZn-Na catalyst achieves the highest CO2 hydrogenation activity and the lowest CO selectivity. The development of supported metal catalysts is important for maximizing catalytic activity and controlling product selectivity. The main function of the support is to improve the dispersion of active metals and the stability of the catalyst. The structure and properties of the support have a significant impact on the activity, selectivity and stability of the catalyst. How to choose a support to improve the performance of CO2 hydrogenation to olefins remains to be studied.
[0003] At present, some Na-promoted iron-based supported catalysts have been applied for relevant patents for CO2 hydrogenation to synthesize light olefins. The following are several reported patents for detailed description: Patent CN116393134A is publicly named: A method for preparing a high-performance alkali metal-modified Fe / ZrO2 catalytic material. The patent reports that Fe and Na / K / Cs are loaded on the surface of ZrO2 as catalysts. The conversion rate in the CO2 hydrogenation reaction is generally not high, about 30%. Patent CN110586108A is publicly named: A catalyst for the co-production of light olefins by hydrogenation of carbon dioxide to gasoline and its preparation method. The patent reports that FeCoNa catalyst is loaded on the surface of γ-Al2O3. The conversion rate in the CO2 hydrogenation reaction is also generally not high, with a maximum of 36.6%. So far, there has been no research report on the use of high entropy layered double hydroxides (HE-LDH) for hydrogenation of carbon dioxide to olefins. Summary of the invention
[0004] In order to solve the problem in the background technology, the present invention adopts a one-step coprecipitation method to react metal salts of six elements with sodium carbonate and sodium hydroxide, and adopts a coprecipitation method to prepare a high-entropy iron-aluminum layered double hydroxide, and after loading sodium iron, a high-entropy iron-aluminum layered double hydroxide loaded with sodium iron catalyst is obtained, which is used for carbon dioxide hydrogenation to olefins, and good results are achieved, especially the O / P aspect has been significantly improved. The prepared catalyst inherits the excellent thermodynamic stability of the high-entropy catalyst and is expected to be well applied in the field of carbon dioxide hydrogenation.
[0005] The present invention provides a method for preparing a high entropy iron-aluminum layered double hydroxide supported iron-sodium catalyst, comprising the following steps:
[0006] A. Fully stir iron salt, cobalt salt, copper salt, zinc salt, manganese salt and aluminum salt in deionized water to obtain a uniformly mixed metal salt solution. The molar relationship of iron salt, cobalt salt, copper salt, zinc salt, manganese salt and aluminum salt is iron:cobalt:copper:zinc:manganese:aluminum=1.5:1.5:1.5:1:1.5:8-9.
[0007] B. Dissolve sodium carbonate and sodium hydroxide in deionized water in a certain proportion and stir to obtain a uniformly mixed alkaline solution.
[0008] C. Add the alkaline solution dropwise into the metal salt solution in step A and stir until the set pH value reaches 8 to 12, and then stir at a certain temperature, specifically at 60° C. for 24 hours.
[0009] D. After stirring, the obtained solution is filtered and washed with deionized water, and then placed in an oven for drying. The reaction conditions are 60-100°C and maintained for 2h-48h.
[0010] E. The product obtained after drying is calcined in a quartz tube furnace under air atmosphere at 600-800° C. for 2-4 h at a rate of 3° C. / min-6° C. / min to obtain a high entropy iron-aluminum layered double hydroxide carrier.
[0011] F. Ball milling the iron salt, sodium salt and the calcined high entropy iron-aluminum layered double hydroxide carrier.
[0012] G. The product obtained after ball milling is placed in a quartz tube furnace for calcination in an air atmosphere at 500-600° C. for 2-4 hours at a rate of 1° C. / min-20° C. / min. After calcination, a high entropy iron-aluminum layered double hydroxide-supported sodium iron catalyst is finally prepared.
[0013] Further, the iron salt described in step A is one or more of ferric chloride trihydrate, anhydrous ferric chloride, ferric nitrate nonahydrate, ferric sulfate pentahydrate, and ferric acetate tetrahydrate. The cobalt salt is one or more of cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt sulfate heptahydrate, and cobalt acetate tetrahydrate. The copper salt is one or more of copper chloride dihydrate, copper nitrate trihydrate, copper sulfate pentahydrate, and copper acetate monohydrate. The zinc salt is one or more of zinc chloride tetrahydrate, zinc nitrate hexahydrate, zinc sulfate heptahydrate, and zinc acetate dihydrate. The manganese salt is one or more of manganese chloride tetrahydrate, manganese nitrate tetrahydrate, manganese sulfate tetrahydrate, and manganese acetate tetrahydrate. The aluminum salt is one or more of aluminum chloride hexahydrate, aluminum nitrate nonahydrate, aluminum sulfate 18hydrate, and aluminum acetate dihydrate.
[0014] Furthermore, the molar ratio of sodium carbonate to sodium hydroxide in step B is 1:2.5.
[0015] Furthermore, in step F, the mass ratio of the iron salt to the high entropy iron-aluminum layered double hydroxide carrier is 2:2-3.
[0016] Furthermore, in step F, the molar ratio of iron to sodium is 7:1.5-2.0.
[0017] The invention provides an application of a high entropy iron-aluminum layered double hydroxide supported iron-sodium catalyst material in chemical catalysis, specifically, an application of obtaining high-value chemicals, especially olefins, through the use of carbon dioxide and hydrogen at high temperature and high pressure.
[0018] It is used as a catalyst in the carbon dioxide hydrogenation reaction. The catalyst is loaded into a catalytic reactor, pre-treated with hydrogen reduction for 18 hours, and then switched to a CO2 / H2 / N2 mixed gas (mixed volume ratio is 23 / 69 / 8), and hydrogenated to olefins at a temperature of 280°C, a pressure of 2.5MPa, and an air velocity of 1650ml / (g*h), and the reaction time is 2h.
[0019] The prepared layer has the following characteristics:
[0020] The present invention adopts a precipitation method plus a ball milling method, uses Na2CO3 and NaOH as precipitants, and adjusts the pH value to precipitate six elements, namely, iron, cobalt, copper, zinc, manganese, and aluminum. CO3 anions and water molecules are restricted in the interlayer structure, and after calcination, HE-LDH is transformed into a spinel structure. First, due to the different precipitation speeds of different elements, different crystal forms will be formed under different pH conditions, which will affect the surface dispersion of the subsequent sodium iron loading; second, the structure forms a layer, which expands the specific surface area and improves the adsorption capacity of carbon dioxide; third, the catalyst is a high entropy structure, which improves the stability of the catalyst in carbon dioxide hydrogenation olefins.
[0021] The method adopted by the present invention is a precipitation method, and the prepared catalyst exhibits good catalytic performance. In the high entropy loaded sodium iron catalyst, iron and copper are used as the active phases of RWGS, sodium improves the alkaline sites on the surface, improves the adsorption of CO2, and the synergistic effect of each element in the carrier plays a certain role in improving the subsequent hydrogenation performance. High entropy oxide (HEO) is a single solid solution composed of five or more elements, and its formation is driven by entropy, giving them excellent thermodynamic stability, unique synergistic effects, diverse phase structures and tunable electronic structures. Compared with traditional oxides, HEO has more oxygen vacancies, which is conducive to the subsequent adsorption of gases and improves the conversion rate. The high entropy loaded sodium iron catalyst prepared by the present invention embodies the high thermal stability of high entropy catalysts, exhibits a higher specific surface area, is simple to prepare, and has low cost. It is easy to scale up experiments and can realize industrial production. The present invention compares traditional oxide carriers and selects HE-LDH as a carrier to achieve high activity and high selectivity in CO2 hydrogenation to generate light olefins.
[0022] The invention provides a high entropy layered double hydroxide supported sodium iron catalyst, which is prepared by the above method. The crystal form of the high entropy layered double hydroxide is iron aluminum spinel, and it is also a pure phase, and the preparation temperature is 700°C, which is lower than the traditional preparation temperature of pure iron aluminum spinel, 1500°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is the XRD pattern of the catalyst of Example 1;
[0024] Figure 2 is the XRD pattern of the catalyst of Example 2;
[0025] Figure 3 is the XRD pattern of the catalyst of Example 3;
[0026] Figure 4 is the XRD pattern of the catalyst of Example 4;
[0027] Figure 5 is the XRD pattern of the catalyst of Example 5;
[0028] Figure 6 The graph of CO2 conversion rate changing with time in the catalytic reaction of the catalysts in Examples 1-5;
[0029] Figure 7 This is the SEM image of the catalyst in Example 3. DETAILED DESCRIPTION
[0030] Example 1
[0031] A. Combine 0.61gFe(NO3)3·9H2O, 0.44gCo(NO3)2·6H2O, 0.36gCu(NO3)2·3H2O, 0.3gZn(NO3)2·6H2O, 0.37gC4H 14 MnO8 and 3.2 gAl(NO3)3·9(H2O) were dissolved in 100 mL of deionized water and stirred vigorously to form a homogeneous solution A.
[0032] B. Dissolve 2.4 g NaOH and 2.544 g Na2CO3 in 60 mL deionized water and stir to obtain a uniformly mixed solution B.
[0033] C. Slowly drip solution B into solution A until pH = 10, and stir the resulting solution at 60°C for 24 hours. D. Filter and wash the stirred solution with deionized water to remove Na ions on the surface, and place the collected solid into a petri dish.
[0034] E. Place the sample in the culture dish in an oven for drying at 60°C for 12 hours.
[0035] F. Take the sample out of the oven, grind it into powder and put it into a tubular furnace for calcination at a temperature of 700°C for 4 hours at a heating rate of 5°C / min. Take it out after calcination and grind it to obtain a high-entropy iron-aluminum layered double hydroxide support.
[0036] G. 2.06 g of high entropy iron-aluminum layered double hydroxide support, 2.83 g of Fe(NO3)3·9H2O and 0.14 g of NaNO3 were ball-milled together.
[0037] H. The sample was taken out from the ball mill and placed in a tubular furnace for calcination at a temperature of 550°C for 4 hours at a heating rate of 2°C / min to finally obtain the catalyst FeNa-HEO-10.
[0038] Experimental operation steps of high-pressure catalytic evaluation system: First, weigh a certain amount of catalyst material and quartz sand, mix them thoroughly, then disassemble the reaction tube in the high-pressure catalytic evaluation system, put a small amount of quartz wool in it from top to bottom, then put in quartz sand, put in the previously mixed catalyst after the height of the quartz sand reaches half the height, then put in quartz sand until the top of the reaction tube, and then put in a small amount of quartz wool at the top. Tighten the screws of each part and reconnect it to the high-pressure catalytic evaluation system. On the premise that the entire system is leak-proof, the above-mentioned catalyst is first reduced by hydrogen, specifically: first reduced by H2, the reduction conditions are 0.4MPa pressure, temperature 400℃, air velocity 1545ml / (g*h) (catalyst 0.4g, after measuring 2.5ml / 14.56s, 2.5 / 14.56*3600 / 0.4 to get the accurate air velocity), after 18h, after the reduction is completed, CO2 / H2 / N2 mixed gas (mixed volume ratio is 23 / 69 / 8) is introduced. Reaction conditions: temperature 280°C, pressure 2.5MPa, space velocity 1650ml / (g*h). Reaction time 100h. The conversion rate of CO2, selectivity of methane and C2 = -C4 = , selectivity for C5+.
[0039] 20 sets of data were collected, and the average values were calculated to be 36.93% for CO2 conversion, 30.72% for methane selectivity, and 30.72% for C2 = -C4 = The selectivity of is 37.01% and the selectivity of C5+ is 22.96%.
[0040] Example 2
[0041] The difference between the catalyst of Example 2 and the catalyst of Example 1 is that in step C, the pH value is reduced from 10 to 8, and the other operations are the same as those of Example 1, to obtain the catalyst FeNa-HEO-8.
[0042] The catalytic reaction process is the same as that in Example 1. The average value of the 20 sets of data obtained in the experiment is taken. The conversion rate of CO2 prepared in Example 2 is 39.15%, the selectivity of methane is 28.48%, and the selectivity of C2 = -C4 = The selectivity of is 36.73% and the selectivity of C5+ is 19.8%.
[0043] Example 3
[0044] The difference between the catalyst of Example 3 and the catalyst of Example 1 is that in step C, the pH value is increased from 10 to 12. The other operations are the same as those of Example 1 to obtain the catalyst FeNa-HEO-12.
[0045] The catalytic reaction process is the same as that in Example 1. The average value of the 20 sets of data obtained in the experiment is taken. The conversion rate of CO2 prepared in Example 3 is 40.03%, the selectivity of methane is 31.25%, and the selectivity of C2 = -C4 = The selectivity of is 39.28% and the selectivity of C5+ is 20.93%.
[0046] Compared with Examples 1 and 3, Example 2 has a relatively low pH value in the preparation conditions, and the incomplete precipitation causes a little aluminum oxide to precipitate from the carrier, which blocks some active sites and promotes secondary hydrogenation. The O / P is the lowest compared to the other two. In addition, the conversion rates of Examples 1-3 are all above 36.6%, which is higher than the conversion rates of the traditional oxide sodium iron supported catalysts in Patents CN116393134A and CN110586108A mentioned in the background technology. This is because there are more oxygen vacancies in the high entropy, which promotes the adsorption of CO2, and is also the advantage of choosing high entropy as a carrier in this patent.
[0047] Example 4
[0048] The difference between the catalyst of Example 4 and the catalyst of Examples 1-3 is that the elements are the same but the preparation methods are different.
[0049] A. Combine 0.4gFe(NO3)3·9H2O, 0.29gCo(NO3)2·6H2O, 0.24gCu(NO3)2·3H2O, 0.3gZn(NO3)2·6H2O, 0.25gC4H 14 MnO8, 0.2gC9H 21 AlO3 and 1g F127 are placed in a ball mill and ball milled.
[0050] B. Take the sample out of the ball mill and place it in a tubular furnace for calcination at 700°C for 4 hours at a heating rate of 5°C / min to obtain a high entropy carrier.
[0051] C. 2.06 g of high entropy carrier, 2.83 g of Fe(NO3)3·9H2O and 0.14 g of NaNO3 were ball-milled together.
[0052] D. Take the sample out of the ball mill and place it in a tubular furnace for calcination at 550°C for 4 hours at a heating rate of 2°C / min. Finally, the catalyst FeNa-HEO is obtained.
[0053] The catalytic reaction process was the same as that in Example 1. The average values of the 20 sets of data obtained in the experiment were taken. The conversion rate of CO2 was 28.61%, the selectivity of methane was 23.33%, and the selectivity of C2 = -C4 =The selectivity of C is 40.85% and the selectivity of C5+ is 21.95%.
[0054] Compared with Example 1-3, in terms of structure, although the carrier components are the same, due to different preparation methods, Example 1-3 adopts the coprecipitation method to form a layered structure, while Example 4 adopts the ball milling method and does not have a layered structure. The XRD of the carrier after calcination shows that Example 4 is not a pure phase, and some aluminum and manganese oxides are precipitated. In terms of catalytic performance, Example 1-3 has a large specific surface area and a higher conversion rate than Example 4. Some oxides are precipitated on the surface of Example 4. Due to the synergistic effect of the elements, the presence of manganese oxide makes C2 = -C4 = The selectivity is higher than others, but the presence of aluminum oxide inhibits some active sites and promotes secondary hydrogenation. The O / P ratio is not high compared to other high entropy methods, and the final yield STY Example 4 is the lowest.
[0055] Example 5
[0056] The difference between the catalyst of Example 5 and the catalyst of Examples 1-4 is that the carrier is changed from high entropy to γ-Al2O3.
[0057] A. Dissolve 6.39 g of Al(NO3)3·9H2O in deionized water and stir at 60°C.
[0058] B. When the solution is completely mixed, heat it to 100°C and add 12.96 ml of ammonia solution dropwise. Continue stirring at room temperature for 12 hours.
[0059] C. The obtained pale off-white precipitate was filtered, washed, and dried at 120°C overnight.
[0060] D. Take the sample out of the oven, grind it into powder and put it into a tubular furnace for calcination. The calcination temperature is 650℃, maintained for 4h, and the heating rate is 2℃ / min, finally obtaining γ-Al2O3.
[0061] E. Ball mill 2.06 g of γ-Al2O3, 2.83 g of Fe(NO3)3·9H2O and 0.14 g of NaNO3 together.
[0062] F. Take the sample out of the ball mill and place it in a tubular furnace for calcination at 550°C for 4 hours at a heating rate of 2°C / min. Finally, the catalyst FeNa-γ-Al2O3 is obtained.
[0063] The catalytic reaction process was the same as that in Example 1. The average values of the 20 sets of data obtained in the experiment were taken. The conversion rate of CO2 was 30.82%, the selectivity of methane was 54.83%, and the selectivity of C2= -C4 = The selectivity of is 1.06% and the selectivity of C5+ is 8.77%.
[0064] Compared with Example 5, the CO2 conversion rate and C2 = -C4 = The selectivity and O / P ratio are significantly improved, and the methane selectivity is also significantly reduced; Examples 1-3 are verified by experiments and show very good catalytic effects and good thermal stability. Compared with Example 4 and Example 5, the catalytic activity is still very good after a long time (100 hours), and it has great potential application in the field of carbon dioxide hydrogenation.
[0065] Comparative Example
[0066] The high entropy carrier in Example 1 was directly subjected to catalytic reaction. The reaction process was the same as that in Example 1. The average value of 20 sets of data obtained in the experiment was taken. The conversion rate of CO2 was 49.23%, the selectivity of methane was 67.78%, and the selectivity of C2 = -C4 = The selectivity of is 0.86% and the selectivity of C5+ is 2.71%.
[0067] Compared with Example 4, Example 1, C2 = -C4 = The selectivity, O / P ratio and STY value are greatly improved, and methanation is also well inhibited, which indicates that after the sodium iron is loaded, iron acts as an active phase and sodium acts as an auxiliary to promote the formation of olefins.
[0068] Table 1 is a table of catalytic performances of Example 1, Example 2, Example 3, Example 4, Example 5, and Comparative Example.
[0069] Table 1
[0070]
[0071]
Claims
1. A method for preparing a high entropy iron-aluminum layered double hydroxide supported sodium iron catalyst, characterized in that: The preparation steps are as follows: (1) fully stirring iron salt, cobalt salt, copper salt, zinc salt, manganese salt and aluminum salt in deionized water to obtain a uniformly mixed metal salt solution; dissolving sodium carbonate and sodium hydroxide in deionized water in a certain proportion and stirring to obtain a uniformly mixed alkaline solution; (2) dropping the alkaline solution into the metal solution and stirring until the set pH value of 8 to 12 is reached, and then stirring at a certain temperature; (3) After stirring, filter and wash, and then put into an oven for drying at 60-100°C for 2h-48h; (4) calcining the product obtained after drying in a quartz tube furnace under air atmosphere at a calcination temperature of 600-800° C. to obtain a high entropy iron-aluminum layered double hydroxide support; (5) ball-milling the iron salt, sodium salt and the high-entropy iron-aluminum layered double hydroxide carrier obtained by calcination, and placing the product obtained after ball-milling in a quartz tube furnace for calcination in an air atmosphere at a calcination temperature of 500-600° C. to prepare a high-entropy iron-aluminum layered double hydroxide supported on iron-sodium catalyst.
2. The method for preparing a high entropy iron-aluminum layered double hydroxide supported sodium iron catalyst according to claim 1, characterized in that: The iron salt is one or more of ferric chloride, ferric nitrate, ferric sulfate, and ferric acetate; the cobalt salt is one or more of cobalt chloride, cobalt nitrate, cobalt sulfate, and cobalt acetate; the copper salt is one or more of copper chloride, copper nitrate, copper sulfate, and copper acetate; the zinc salt is one or more of zinc chloride, zinc nitrate, zinc sulfate, and zinc acetate; the manganese salt is one or more of manganese chloride, manganese nitrate, manganese sulfate, and manganese acetate; and the aluminum salt is one or more of aluminum chloride, aluminum nitrate, aluminum sulfate, and aluminum acetate.
3. The method for preparing a high entropy iron-aluminum layered double hydroxide supported sodium iron catalyst according to claim 1, characterized in that: The molar relationship of iron salt, cobalt salt, copper salt, zinc salt, manganese salt and aluminum salt is iron:cobalt:copper:zinc:manganese:aluminum=1.5:1.5:1.5:1:1.5:8~9.
4. The method for preparing a high entropy iron-aluminum layered double hydroxide supported sodium iron catalyst according to claim 1, characterized in that: The molar ratio of sodium carbonate to sodium hydroxide is 1:2.
5.
5. The method for preparing a high entropy iron-aluminum layered double hydroxide supported sodium iron catalyst according to claim 1, characterized in that: The pH value of step (2) is 12.
6. The method for preparing a high entropy iron-aluminum layered double hydroxide supported sodium iron catalyst according to claim 1, characterized in that: In step (5), the mass ratio of the iron salt to the high entropy iron-aluminum layered double hydroxide support is 2:2-3; The molar ratio of iron salt to sodium salt is 7:1.5-2.
0.
7. Use of a high entropy iron-aluminum layered double hydroxide supported on sodium iron catalyst prepared according to the method according to any one of claims 1 to 6 in carbon dioxide hydrogenation catalysis.
8. The use according to claim 7, characterized in that: The catalyst was filled into the reactor, and H2 was first introduced for reduction, and then a mixture of CO2 and H2 was introduced, with the volume ratio of CO2 and H2 being 1:
3. The hydrogenation reaction was carried out under the reaction conditions of temperature 280°C and pressure 2.5MPa.
Citation Information
Patent Citations
Catalyst for co-production of low carbon alkenes from carbon dioxide hydrogenation to gasoline and preparation method of catalyst
CN110586108A
Preparation method of high-performance alkali metal modified Fe / ZrO2 catalytic material
CN116393134A
Cited By
High-entropy layered metal hydroxide composite material as well as preparation method and flame-retardant and smoke-suppression application thereof
CN120058006A
